Znaczenie słowa i zasada wewnętrznej motywacji cech semantycznych - Tokarski, Ryszard (Wydawnictwo „Poznańskie Studia Polonistyczne” i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The meaning of a word has a layered structure with the clearly distinguished center (prototype, lexical meaning) and – the further towards the peripheries – with semantic connotations more and more weak-established in the system. Giving-up of the purely structuralist understanding of connotations (verified by semantic and morphological derivatives, collocations, repeatable lexical oppositions, or various tests) has created a danger that semantically irrelevant components may be recognized as relevant qualities. The article proposes a rule for verification of weak connotations. Underlying the principle of internal motivation of qualities is the conviction that the meaning of a word is internally structured, while each quality, especially weak connotations, are motivated by the overall structure of meaning and are explained in the context of this structure.
The principle of internal motivation (predictability) of semantic qualities
Keywords: semantic definition; semantic connotation; word meaning